Stratifin accelerates progression of lung adenocarcinoma at an early stage - Shiba-Ishii, Aya (Mol Cancer, 2015)
BACKGROUNDS: Adenocarcinoma in situ (AIS) of the lung has an extremely favorable prognosis. However, early but invasive adenocarcinoma (eIA) sometimes has a fatal outcome. We had previously compared the expression profiles of AIS with those of eIA showing lymph node metastasis or a fatal outcome, and found that stratifin (SFN, 14-3-3 sigma) was a differentially expressed gene related to cell proliferation. Here, we performed an in vivo study to clarify the role of SFN in initiation and progression of lung adenocarcinoma. FINDINGS: Suppression of SFN expression in A549 (a human lung adenocarcinoma cell line) by siSFN significantly reduced cell proliferation activity and the S-phase subpopulation. In vivo, tumor development or metastasis to the lung was reduced in shSFN-transfected A549 cells. Moreover, we generated SFN-transgenic mice (Tg-SPC-SFN(+/−)) showing lung-specific expression of human SFN under the control of a tissue-specific enhancer, the SPC promoter. We found that Tg-SPC-SFN(+/−) mice developed lung tumors at a significantly higher rate than control mice after administration of chemical carcinogen, NNK. Interestingly, several Tg-SPC-SFN(+/−) mice developed tumors without NNK. These tumor cells showed high hSFN expression. CONCLUSION: These results suggest that SFN facilitates lung tumor development and progression. SFN appears to be a novel oncogene with potential as a therapeutic target. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12943-015-0414-1) contains supplementary material, which is available to authorized users.